Analisis Regresi Linier Tingkat Pengangguran di Indonesia Periode 2024–2025 - Budi Abdullah; Reysya Yusdianingsih; Nandita Saskya; Muhammad Muarif; Juliana Handayani br. Simatupang; Jumadi Jumadi; Muhammad Risky (Jurnal Hukum dan Sosial Politik, 2026)
This study aims to analyze the unemployment rate in Indonesia during the 2024–2025 period using a linear regression approach based on data from the National Labor Force Survey (Sakernas). The variables used include the labor force, employed population, labor force participation rate (LFPR), and open unemployment rate (OUR). The results show that the labor force increased from 149.38 million in February 2024 to 155.27 million in November 2025, followed by an increase in employed population from 142.18 million to 147.91 million in the same period. Meanwhile, the open unemployment rate decreased from 4.76 percent in February 2025 to 4.74 percent in November 2025. The analysis indicates that the increase in labor force accompanied by higher employment absorption contributes to reducing unemployment, although the decline remains relatively small. Overall, the regression results show that labor market dynamics are influenced by the interaction between labor force growth and the economy’s capacity to absorb labor.